Pengaruh Asimetri Informasi Terhadap Praktik Manajemen Laba pada Perusahaan Perbankan Publik yang Terdaftar di Bursa Efek Jakarta - Rahmawati Rahmawati; Yacob Suparno; Nurul Qomariyah (The Indonesian Journal of Accounting Research, 2013)
The purpose of this research is to examine the effect of information asymmetry on earnings management. Result of this research can benefit to theory development and management. Accountancy data are collected from ICMD (Indonesian Capital Market Directory) and stock prices data which are provided by Center Capital Market Reference (PRPM) of Jakarta Stock Exchange.  The sample of this research are public Indonesian banking firms in 2000 until 2004.The results show that slope are significant (p value < 0.05), so Ho is rejected and Ha is accepted or available significant positive effect between information asymmetry and earnings management. R2 value is 0.3584 that mean 35.84% dependent variable earnings management can be explained by independent variable information asymmetry, and control variable CFVAR, GROWTH, SIZE, MKTBV and then 64.16% explained by another factor out side in the regression model but in the regression between dependent variable of earnings management with control variable resulted R2 value 0.417 and then in the regression between dependent variable earnings management with independent variable information asymmetry resulted R2 value 0.18 so control variable more explaine dependent variable earnings management. Independent variable information asymmetry has significant positive effect and can explaine dependent variable earnings management 18%.